THE FACTORS CAUSING ISCHEMIC HEART DISEASE AMONG THE POPULATION OF THE SOUTHERN ARAL SEA REGION HEVE BEEN STUDIED - Ismailov, K.Y. (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
The incidence and mortality of cardiovascular diseases (CVD) in Uzbekistan continue to grow and remain high. Only multifactorial preventive measures, early identification of risk factors (RF) and individuals predisposed to CVD, and changes in the lifestyle of the population through active and reasoned propaganda activities can change the situation in a positive direction. One of the factors contributing to the development of cardiovascular diseases is excess body weight and obesity. It is known that obesity is one of the most common chronic diseases in the world and leads to the development of cardiovascular diseases. Early detection and elimination of risk factors for cardiovascular disease can reduce morbidity and mortality. This article examines the development of coronary heart disease in overweight and obese adult patients by interpreting the results of electrocardiography and body weight by measuring weight (kg) and height (cm2).